Earthquake Disaster Risk Analysis for Mitigation Efforts in Seram and Buru Islands, Maluku - Matheus Souisa; Sisca M. Sapulete; Learsi A. Siahaya (Postgraduate, University of Mataram, 2023)
Earthquakes occur due to the sudden release of energy from within the earth causing seismic waves. Earthquake activity with a magnitude Â³ 3.5 SR is grouped over 21 years from 2000-2020 to determine the level of seismicity in Seram Island, Buru Island, and surrounding areas. The area of seismic activity is clustered over three blocks. The purpose of this research is to determine the seismicity level and mitigation model in each block in the research area. The results showed that seismic activity in the study area with shallow earthquakes was mostly in Block II as many as 1195 times (40.4%) and Block III as many as 1135 times (38.4%). This block is estimated to have the potential for a tsunami to occur. Mitigation efforts to reduce the risk of earthquakes are by implementing a resilient-elastic building system and the location of settlements from the coastline > 100 m with a topography of at least 25 meters